Amplitude evaluated with head-toe distance in relation to where circles are performed on pommel horse - Fujihara, T. (ISBS Proceedings Archive (Michigan), 2020)
Gymnastic judging is likely to integrate an objective measurement, so appropriate performance variables will become critical for fair and valid judging. As noted in literature, head-toe distance (HTD) is a potential variable to evaluate the amplitude of horizontal rotation on pommel horse performances. This study investigates how HTD varies when circles were performed on different positions on the pommel horse. Kinematic data for eight different types of circles performed by three gymnasts were recorded using a Kinect set that was placed above the pommel horse during regular training. As a result, the different profile of HTD were found depending on where the gymnasts performed circles, demonstrating the possible influences of types of circles on HTD. The importance of better understanding and careful use of such a performance variable was emphasised.